EVALUASI TINGKAT KEPUASAN PASIEN TERHADAP PELAYANAN KEFARMASIAN DI KLINIK X MENGGUNAKAN APLIKASI E-SERVQUAL BERBASIS WEB - Rianto, Leonov; Al'Qarana, Gilang; Sabrina, Alifa (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2019)
In an effort to improve the quality of service, patient satisfaction can be measured by the SERVQUAL (SERVICE QUALITY) method by making a comprehensive customer satisfaction assessment survey for services in the field of goods and services that prioritize pharmaceutical services. Customer satisfaction analysis is based on five dimensions of service quality, namely responsiveness, reliability, assurance, empathy, and tangible. The formulation of the problem in this study wanted to find out how patient satisfaction with pharmacy services in clinic X. The purpose of this study was to describe patient satisfaction with pharmacy services in clinic X. Using descriptive quantitative methods to determine the level of patient satisfaction with pharmaceutical services using questionnaires as instruments Study data on patient visits were treated at 3 months beginning in 2018 in January 2,970 patients, February 2,868 patients, and March 3,304 patients. Based on data that has been recapitulated in a system by web-based e-SERVQUAL application and its validity has been tested, the percentage of each variable is evenly distributed in the range of 70%, on the dimensions of attitude and appearance. , 20% of patients were satisfied, in the dimension of drug waiting time, 73.90% of patients were satisfied, on the assurance dimension 74.45% of patients were satisfied, on the dimensions of empathy satisfied patients were 73.50%, on the dimensions of facilities and patient facilities were satisfied , 87%. From these results, the patient is satisfied with the overall dimensions of service, the greatest level of satisfaction is in the dimensions of attitude and appearance, and the smallest level of satisfaction is on the dimensions of facilities and facilities, it can be concluded that the percentage of 74.14% is in the predicate satisfied.